Analysis of Integrated Lecture Minutes Recording System Analysis Based on RFID - Irfan Sudahri Damanik; Eka Irawan (IJISTECH (International Journal of Information System and Technology), 2020)
RFID (Radio Frequency Identification) is an identification technology for wireless data retrieval using radio waves. RFID is part of the development of semiconductor technology that is integrated with informatics systems. In the college environment, especially in the academic sector, there is often a problem with the process of recapitulation of attendance notes for lectures which is not effective and efficient. Therefore this research aims to build an information system that utilizes semiconductor RFID technology. The RFID tag used is a card that will be used as a substitute for a student ID card (KTM) in which there is a unique code that is used as the ID number of each student. This RFID tag data will be integrated with the database system so that the attendance process for lecture minutes becomes more effective and efficient. This is because students carry out the attendance process by attaching the KTM to the RFID reader, which will read the RFID tag on the KTM and store it in the database. So that the process of attendance recapitulation of lecture events becomes easier because the data is automatically stored in the database.